Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Telkom Indonesia Witel Bogor - Najwa Nabila; Ade Sri Mulyani (Master Manajemen, 2024)
PT Telkom Indonesia (Persero), Tbk is a State-Owned Enterprise (BUMN) that provides telecommunication network services and information and communication technology (ICT) in Indonesia. The focus of this research is on the performance of employees of PT Telkom Indonesia Witel Bogor. Employee performance is estimated to be influenced by leadership style and work discipline of PT Telkom Indonesia Witel Bogor. The method of collecting data in the preparation of the thesis is the observation method and questionnaire with the analysis method in the form of quantitative analysis with data collection techniques using the Slovin formula. The population used was 43 respondents using a questionnaire in the Likert scale unit. In data processing for analysis, the application of the SPSS 20 program was used with multiple linear regression analysis techniques with the results Y = 1.022 + 0.034 X1 + 0.804 X2 which included data quality tests, classical assumption tests, partial hypothesis tests with T results of 7.337 (X1) and 10.016 (X2). Simultaneously the two independent variables obtained an F calculated of 49.023. In the determination coefficient test, the two independent variables had an effect of 70.5% on employee performance.